Assessing rehabilitation potential of the masticatory musculature in patients with temporomandibular myofascial pain syndrome: A randomized prospective controlled study - E. N. Iarygina; V. V. Shkarin; Yu. A. Makedonova; S. V. Dyachenko (Кубанский научный медицинский вестник)
Background. Selecting therapy for temporomandibular myofascial pain syndrome must be carefully justified, since functional impairments may be compensated and acceptable for the patient. Treatment for patients with temporomandibular myofascial pain syndrome is primarily aimed at improving the psychological and physical state of the patient, as well as restoring lost functions, which is defined by the rehabilitation potential. Along with eliminating the chronic pain, the treatment is required to activate the compensatory mechanisms of the body responsible for restoring lost functions. Objective. To assess the rehabilitation potential of the masticatory musculature in patients with temporomandibular myofascial pain syndrome over the course of treatment. Methods. 74 patients diagnosed with temporomandibular myofascial pain syndrome participated in a randomized prospective controlled study conducted from 2021 to 2024. The patients were divided into two groups based on the therapeutic regimen applied. Group I comprised 37 patients who received standard therapy, including the administration of non-steroidal anti-inflammatory drugs and blocking the motor fiber of the third branch of the trigeminal nerve. Group II included 37 patients who additionally participated in a device-assisted facial and mandibular gymnastics. The study was supervised by the Advisory Council of the Department of Dentistry of the Institute for Continuous Medical and Pharmaceutical Education and the Department of Surgical Dentistry and Maxillofacial Surgery, Volgograd State Medical University, Russian Federation. The study was conducted at the Volgograd Regional Clinical Dental Polyclinic and the Dental Clinical Diagnostic Center, Volgograd State Medical University, Russian Federation. The duration of follow-up for each patient comprised 6 months. The data analysis was carried out prior to treatment, as well as in 14 days, 1 month, 3 months, and 6 months after treatment. The masticatory muscles rehabilitation potential was assessed using various methodologies, including psychological evaluations (assessment of psycho-emotional state via the Perceived Stress Scale), clinical measures (palpatory algometry, evaluation of muscle functional activity according to the Modified Ashworth Scale, maximum mouth opening, 3D dental scanning, and radiological examination), as well as functional assessments (myotonometrical and electromyographic tests). The applied methodology allowed for evaluating pain management, restoring masticatory muscle functionality, a decrease in the mean amplitude of the temporalis and masseter muscles, and an increase in maximal mouth opening. Statistical analysis was performed using Microsoft Excel 2017 (Microsoft, USA), with a significance level at p ≤ 0.05. Results. According to the analysis of psychological stress, all patients exhibited disturbances in their psycho-emotional state, with an average stress score of 39.4 ± 4.1, indicating its high intensity. Based on these findings, the patients were referred for consultation with a psychotherapist. During the treatment, all groups demonstrated positive outcomes within a short observation period (within 14 days after the start of treatment). However, pain relief occurred more intensively with the administration of a 2% lidocaine solution (3–4 ml) for nerve block. In the long term, the dynamics of functional activity changes varied among the compared groups. Notably, Group II (patients received a device-based complex of facial and mandibular gymnastics) revealed a statistically significant difference in both pre-treatment measurements and the control group indications. A persistent reduction in the mean amplitude of the temporal and masseter muscles, as well as their symmetry index, torsional index, and masseteric index, was observed. Clinically, this correlated with an improvement, implying a decrease in the severity of pain. In contrast, Group I showed changes in values that were close to the initial parameters, marked by a decrease in rehabilitation potential. Improvements in clinical and functional assessment indicators suggest the activation of compensatory mechanisms and enhanced functionality of the masticatory muscles underpinned by alleviating the temporomandibular myofascial pain through facial and mandibular gymnastics. Conclusion. The study results justified the use of device-assisted facial and mandibular gymnastics in the treatment of temporomandibular myofascial pain syndrome to be safe and effective in terms of rehabilitation potential. The standard treatment was established to be most effective within the short-term period (up to 14 days from the start of treatment), while the suggested regimen activates the compensatory mechanisms of the body. Consequently, the management strategy for patients with this pathology should consider the individual resources and rehabilitation potential, as well as social activity and compliance of the patients.